Lexical borrowings in the component structure of dialect idioms (on the material of the artistic works of the West Ukrainian writers of the end of XIX – beginning of XX centuries) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article is about the dialect phraseological units with the components-loanwords, which were recorded in works of art of L. Martovich, V. Stefanik, G.  Hotkevich, M.Cheremshina. Interrelations of Ukrainian with other national languages, ways of loan of words and the stylistic potential of dialect phraseological units are investigated.
Keywords: dialect phraseological unit; loanwords; component structure of phraseological units; art text